Isolation, Characterization And Identification Of Anti-Amylase Peptides From Cumin Seeds (Cuminum Cyminum) - Siow, Hwee Leng (2018)
The main objective of this thesis was to discover novel anti-amylase peptides from cumin (Cuminum cyminum) seeds. This spice seed is high in protein and has a long history of use in traditional medicine, especially in treating diabetes, making it potential precursor proteins for producing peptides with potent bioactivities that can impart health-promoting effects beyond their nutritional values. The first phase of this study comprises fundamental studies on the extraction and characterization of soluble protein from cumin seeds. Through response surface methodology (RSM), a maximum yield of 44.98 mg soluble protein/g defatted sample was obtained under a condition of 0.6 h, 26.3 ˚C, and buffer-to-sample ratio of 10 mL/g.